Från konsument till medproducent - Sjöblom, Jenny (2015)
Community Supported Agriculture (CSA) is an unconventional model of agriculture expected to contribute to a more sustainable food supply and a sustainable landscape; the development of rural areas; a stronger relationship between producer and consumer and a healthier diet. This study, with a focus on food production and the link between the producer and consumer, describes the origin and current development of CSA in Sweden, including the prerequisites for CSA in a Swedish context. Organizations and entrepreneurs working with CSA and related projects are identified and interviewed. The notion of CSA in Sweden is still in its infancy, but a rapidly growing interest currently can be detected. The fact that the identified CSAs are found in different Swedish regions with variations in degree of urbanization and intensity of agriculture indicates that the prerequisites are there for the concept to grow, both in rural as well as urban areas. This study suggests that the concept of CSA could be used as a means to create sustainable food from soil to table. However, there are some implications regarding the accessibility of CSA to the broader population, which needs to be further explored.